2001
DOI: 10.1073/pnas.161173098
|View full text |Cite
|
Sign up to set email alerts
|

PNA interference mapping demonstrates functional domains in the noncoding RNA Xist

Abstract: The noncoding RNA Xist has been shown to be essential for X-chromosome inactivation and to coat the inactive X-chromosome (Xi). Thus, an important question in understanding the formation of Xi is whether the binding reaction of Xist is necessary for X-chromosome inactivation. In this article, we demonstrate the failure of X-chromosome silencing if the association of Xist with the X-chromosome is inhibited. The chromatin-binding region was functionally mapped and evaluated by using an approach for studying nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 41 publications
7
71
1
Order By: Relevance
“…In keeping, we propose that mH2A may bind RNA through its hinge domain, and the resulting negative charge caused by phosphorylation (T128ph, S137ph, and/or yet unidentified sites) might abrogate its ability to bind RNA, consistent with its exclusion from the Xi. Although the ability of mH2A (and its hinge domain) to bind RNA is unclear, several studies have shown that its localization to the Xi depends on the Xist RNA: conditional deletion of Xist during X inactivation or abolishing the ability of Xist to bind the Xi prevent mH2A association with the Xi, and ectopic expression of Xist on autosomes results in the recruitment of mH2A to these ectopic sites (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping, we propose that mH2A may bind RNA through its hinge domain, and the resulting negative charge caused by phosphorylation (T128ph, S137ph, and/or yet unidentified sites) might abrogate its ability to bind RNA, consistent with its exclusion from the Xi. Although the ability of mH2A (and its hinge domain) to bind RNA is unclear, several studies have shown that its localization to the Xi depends on the Xist RNA: conditional deletion of Xist during X inactivation or abolishing the ability of Xist to bind the Xi prevent mH2A association with the Xi, and ectopic expression of Xist on autosomes results in the recruitment of mH2A to these ectopic sites (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the A-repeat region was recently shown to have most likely originated as an endogenous retrovirus, ERVB5 (Elisaphenko et al 2008). In contrast, the localization of XIST seems to be dependent on sequences more dispersed throughout the transcript (Wutz et al 2002), although a later study using targeting antisense oligonucleotides implicated the murine-specific C-repeat region in correct targeting through unknown mechanisms (Beletskii et al 2001). This targeting is mediated by the specific interaction of repeat C with the transcription factor, YY1, that directs XIST to specific genomic loci through DNA binding (Jeon and Lee 2011).…”
Section: Direct Evidence For Te-derived Functional Domains In Lncrnasmentioning
confidence: 99%
“…Repeat C is located 3 kb downstream of repeat A and contains 14 tandem repeats of a C-rich sequence with ∼90% interrepeat homology. Previous work showed that treating cells for 6 d with an antisense peptide nucleic acid (PNA) against repeat C led to loss of Xist from Xi heterochromatin (13), suggesting that the repeat C region may harbor an essential element. Curiously, it has also been shown that deleting repeat C on an Xist transgene has no effect on XCI (11).…”
mentioning
confidence: 99%